Sistema de Alerta Agrícola en el valle de San Lorenzo, Tambogrande Agricultural Alert - Dedios y Cols., Ninell (2019)
With the aim of providing updated agrometeorologic information to land workers, which would minimize or avoid losses caused by meteorological extreme agents such as droughts and floods or climate change related events, including also the harmful assaults of plagues or diseases to crops, the national service of meteorology and hydrology of Peru (senamhi) implemented a system for agrometeorologic alert. in this respect senami developed workshops for the development and training of farmers with the goal that they learn to use the information generated to make suitable decisions.